Performance Evaluation of Micro-Aerobic Hydrolysis of Mixed Sludge: Optimum Aeration and Effect on Its Biochemical Methane Potential - Ojeda-Reyes, O; Huilinir-Curio, C; Castillo-Reyes, A; Montalvo-Martinez, S (Taylor and Francis Inc., 2016)
This study evaluated the performance of a micro-aerobic hydrolysis of mixed sludge and its influence as a pretreatment of this waste for its subsequent anaerobic digestion. Three experimental series were carried out to evaluate the optimum micro-aeration levels in the range from 0.1 to 0.5 air volume/min.reactor volume (vvm) and operation times within the range of 24–60 h. The maximum methane yield [35 mL CH4/g volatile suspended solids (VSS) added] was obtained for an aeration level of 0.35 vvm. This methane yield value increased 114% with respect to that obtained with the non-aerated sludge. In the micro-aeration process carried out at an aeration level of 0.35 vvm, increases in soluble proteins and total sugars concentrations of 185% and 192% with respect to their initial values were found, respectively, after 48 h of aeration. At the above micro-aerobic conditions, soluble chemical oxygen demand (CODS) augmented 150%, whereas VSS content decreased until 40% of their initial respective values. Higher COD increases and VSS decreases were found at 60 h of micro-aeration, but the above parameters did not vary significantly with respect to the values found at 48 h. © 2016 Taylor & Francis Group, LLC.